New Media-Based Tourism Marketing Communication of Curiak Island Mangrove Forest in Increasing Tourist Awareness - Lalita Hanief; Achmad Bayu Chandrabuwono; Bambang Dwi Waluyo; Noviana Sari; Siti Wida Ningsih; Alfian Al Azhar (Metacommunication: Journal of Communication Studies, 2025)
Curiak Island presents nature tourism with a wealth of flora and fauna typical of South Kalimantan, namely the Proboscis Monkey and Rambai Mangrove. Curiak Island is a research center for proboscis monkeys, an endemic fauna of South Kalimantan. Curiak Island ecotourism is not widely known to the people of South Kalimantan. The purpose of this research is to find out the new media-based tourism marketing communication of mangrove forest tourism on Curiak Island in increasing tourist awareness. Data collection techniques are interviews, documentation and literature studies. The research method uses a qualitative approach with descriptive type. The research informants were the manager of the Curiak Island mangrove forest tour, the Barito Kuala Regency Tourism Culture, Youth and Sports Office and Curiak Island tourists. Data analysis techniques using Manual Data Analysis Procedure (MDAP) in the form of daily notes, transcripts, coding, categories, themes, and memos. The results of the study are marketing communication of Curiak Island using new media in the form of Instagram, Facebook and YouTube. Curiak Island is a special interest tour intended for researchers and study groups. Tourist attractions offered in the form of planting mangroves, seeing the life of proboscis monkeys in the wild, observing birds and reptiles